Fudge-a-mania - Blume, Judy (New York : Dutton Children's Books, 1990)
Peter Hatcher describes his family's Maine vacation highlighted by the antics of his younger brother Fudge and the presence of his sworn enemy Sheila Tubman and her family
Keywords: Vacations -- Fiction; Siblings -- Fiction; Family life -- Fiction; Humorous stories; Maine -- Fiction